2021
DOI: 10.1002/clc.23543
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention and 30‐day unplanned readmission with chest pain in the United States (Nationwide Readmissions Database)

Abstract: Percutaneous coronary intervention (PCI) improves anginal chest pain in most, but not all, treated patients. PCI is associated with unplanned readmission for angina and non‐specific chest pain within 30‐days of index PCI. Patients with an index hospitalization for PCI between January–November in each of the years 2010–2014 were included from the United States Nationwide Readmissions Database. Of 2 723 455 included patients, the 30‐day unplanned readmission rate was 7.2% (n = 196 581, 42.3% female). This includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Kwong et al (2019) suggested that PPCP is likely due to various procedural events, such as abrupt vessel closure, coronary vasospasm, side branch closure, dissection, distal thromboembolism, slow flow, focal vessel stretch, and adventitial injury, which are common with newer devices such as atherectomy and stenting. Nevertheless, PPCP is common even in the absence of procedural events and is commonly attributed to causes related to vasospasm or coronary artery distention (Sykes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kwong et al (2019) suggested that PPCP is likely due to various procedural events, such as abrupt vessel closure, coronary vasospasm, side branch closure, dissection, distal thromboembolism, slow flow, focal vessel stretch, and adventitial injury, which are common with newer devices such as atherectomy and stenting. Nevertheless, PPCP is common even in the absence of procedural events and is commonly attributed to causes related to vasospasm or coronary artery distention (Sykes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have found comorbidities and smoking are risk factors for readmission [ 5 ], predictor models for the readmission of ACS were scarce. Besides, current research mainly focused on the prognostic factors of a specific type of ACS [ 6 ], or a single predictor of short-term or long-term prognosis of ACS, such as decreased glomerular filtration rate (GFR) and increased urinary micro-protein/creatinine ratio [ 7 ], the level of mean platelet volume [ 8 ], etc.…”
Section: Introductionmentioning
confidence: 99%